THE EDUCATION OF HONESTY IN THE PERSPECTIVE OF THE HOLY QURAN (Study of Surah Al-’ Ankabut) - Wahdi, Achyar Zein, Syamsu Nahar (EDU-RILIGIA: Jurnal Ilmu Pendidikan Islam dan Keagamaan, 2019)
Abstract: writing a thesis entitled the education of honesty in the perspective of the Koran (thestudy of surah al-’ Ankabut), aims to study the Qur’anic verses about honesty in surah al-’Ankabut. In the writing of the Thesis, the author uses the method of library (library research),using analytical techniques, that is done by collecting data, especially from the Holy Quranand Tafsir and of books related to the theme research to be able to draw a conclusion, eitherdeductive or inductive. The results showed that: 1. The Qur’an describes in surah al-’ Ankabutabout those people who are given God’s test of life, in order to find out who is a believer andwho is a kaafir and also a hypocrite and who is honest and who is a liar. The exam is Sunnatullahapplicable to every human being the unavoidable anyone, but God never test his servantsbeyond the limits of his abilities, just the way menyikapinya it does correctly or mendustakannya.2. then God pointed out earlier, namely the story of the prophets and their followers as a pilotbetween honest people and Liars, people who are steadfast in truth and those who oppose thetruth so that it becomes a lesson and get wisdom from that event. 3. God has made manperfect among other creatures including one of them there is the nature of honesty. As believersshould be able to keep the mandate in a way fortify yourself by reading the Holy Quran as wellas mentadabburi meaning and also founded 30ru, maintaining social relationships and docharity saleh to avoid nature liars and always istiqomah in upholding the truth and honesty.It’s good to God and also sesame man.Key Word: Education Honesty and Holy Quran